2022
DOI: 10.1097/cce.0000000000000683
|View full text |Cite
|
Sign up to set email alerts
|

Role of Early Enteral Nutrition in Mechanically Ventilated COVID-19 Patients

Abstract: OBJECTIVES: Current guidance recommends initiation of early enteral nutrition (early EN) within 24–36 hours of ICU admission in critically ill COVID-19 patients. Despite this recommendation, there is quite limited evidence describing the effect of early EN on outcomes in COVID-19 patients. The association between early EN (within 3 d post intubation) and clinical outcomes in adult COVID-19 patients requiring mechanical ventilation (within 2 d post ICU admission) was evaluated. DESIGN: We performed a nationwi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 13 publications
(20 reference statements)
0
5
0
1
Order By: Relevance
“…Evidence shows that EEN can lead to shorter ICU and hospital stays, fewer mechanical ventilation days, and decreased hospital expenditure. 23,24 However, less is known about EEN's effectiveness on postsurgery outcomes among children born with GI malformation. This systematic review and meta-analysis found that the experimental group receiving EEN had shortened hospital stays, early fecal movement, and reduced postoperative wound infections.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence shows that EEN can lead to shorter ICU and hospital stays, fewer mechanical ventilation days, and decreased hospital expenditure. 23,24 However, less is known about EEN's effectiveness on postsurgery outcomes among children born with GI malformation. This systematic review and meta-analysis found that the experimental group receiving EEN had shortened hospital stays, early fecal movement, and reduced postoperative wound infections.…”
Section: Discussionmentioning
confidence: 99%
“…Early enteral nutrition is recommended to prevent VAP in critically ill non-COVID-19 patients ( Klompas et al, 2014b ) and critical COVID-19 patients ( Haines et al, 2022 ). A study of real-world clinical practice showed that early enteral nutrition within 3 days after invasive mechanical ventilation can shorten the time of invasive mechanical ventilation and improve the outcome of COVID-19 patients ( Haines et al, 2022 ).…”
Section: Drug Prevention Of Ventilator-associated Pneumonia In Covid-...mentioning
confidence: 99%
“…Early enteral nutrition is recommended to prevent VAP in critically ill non-COVID-19 patients ( Klompas et al, 2014b ) and critical COVID-19 patients ( Haines et al, 2022 ). A study of real-world clinical practice showed that early enteral nutrition within 3 days after invasive mechanical ventilation can shorten the time of invasive mechanical ventilation and improve the outcome of COVID-19 patients ( Haines et al, 2022 ). The mechanisms of early enteral nutrition in preventing VAP may involve reducing pathogen colonization and bacterial translocation through facilitating intestinal peristalsis and maintaining intestinal mucosal structure and barrier function.…”
Section: Drug Prevention Of Ventilator-associated Pneumonia In Covid-...mentioning
confidence: 99%
“…Moreover, supplementation of enteral nutrition with probiotics may decrease septic complications. In patients with COVID-19 requiring mechanical ventilation, early enteral nutrition is associated with earlier liberation from ventilator support, shorter intensive care unit and hospital stay and decreased cost[ 63 , 64 ].…”
Section: Do We Need To Change the Diagnostic And Therapeutic Approach?mentioning
confidence: 99%